2019
DOI: 10.3389/fpsyt.2019.00286
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction in Serotonergic and Noradrenergic Systems and Somatic Symptoms in Psychiatric Disorders

Abstract: Somatic symptoms include a range of physical experiences, such as pain, muscle tension, body shaking, difficulty in breathing, heart palpitation, blushing, fatigue, and sweating. Somatic symptoms are common in major depressive disorder (MDD), anxiety disorders, and some other psychiatric disorders. However, the etiology of somatic symptoms remains unclear. Somatic symptoms could be a response to emotional distress in patients with those psychiatric conditions. Increasing evidence supports the role of aberrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 108 publications
(102 reference statements)
1
37
0
3
Order By: Relevance
“…The monoaminergic hypothesis is based on a partial or total deficit of 5-HT or NE in the central nervous system (CNS) (128,129). Somatic symptoms such as muscle tension, neuropathic and musculoskeletal pain, fatigue, or dizziness are common in MDD and GAD among other psychiatric disorders as result of aberrant 5-HT and NE neurotransmission (130). Regarding pain, antinociception and pronociceptive modulation occurs through 5-HT receptors, in both the central and peripheral nervous systems (131).…”
Section: Discussionmentioning
confidence: 99%
“…The monoaminergic hypothesis is based on a partial or total deficit of 5-HT or NE in the central nervous system (CNS) (128,129). Somatic symptoms such as muscle tension, neuropathic and musculoskeletal pain, fatigue, or dizziness are common in MDD and GAD among other psychiatric disorders as result of aberrant 5-HT and NE neurotransmission (130). Regarding pain, antinociception and pronociceptive modulation occurs through 5-HT receptors, in both the central and peripheral nervous systems (131).…”
Section: Discussionmentioning
confidence: 99%
“…It was well established that the alteration of various behaviors in anxiety disorders including appetite, mood, sleep, and cognitive function have been linked to the serotonergic system (Liu Y. et al, 2018;Liu et al, 2019). Serotonin receptors are FIGURE 4 | The interaction networks of enriched biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…It was well established that the alteration of various behaviors in anxiety disorders including appetite, mood, sleep, and cognitive function have been linked to the serotonergic system ( Liu Y. et al, 2018 ; Liu et al, 2019 ). Serotonin receptors are prevalent throughout the nervous system and the periphery, and they potentially control the serotonergic neurotransmission throughout the brain and neuronal activity to alleviate neuropsychiatric disorders ( Okazawa et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…5-HT is involved in vascular function, proper cardiac function, gastrointestinal function, reproduction, and pregnancy [16]. It is released from the presynaptic nerve terminal and 5-HT transporter receives the signal [17,18]. The decreased levels of the neurotransmitter are proposed to be associated with somatic symptoms [17,18].…”
Section: Antisocial Personality Disorder and Somatic Symptom Disordermentioning
confidence: 99%
“…It is released from the presynaptic nerve terminal and 5-HT transporter receives the signal [17,18]. The decreased levels of the neurotransmitter are proposed to be associated with somatic symptoms [17,18]. It has previously been found that the amount of right orbitofrontal serotonin transporter expressed in the prefrontal cortex region is positively correlated with somatization and the development of SSD [18].…”
Section: Antisocial Personality Disorder and Somatic Symptom Disordermentioning
confidence: 99%